Social Movement of Mandar People as a Struggle in Processof Forming West Sulawesi Province - KAMBO, GUSTIANA (Universitas Muhammadiyah Yogyakarta, 2014)
This paper examines the dynamics of ethnicity in SouthSulawesi. Mandar is a tribe (ethnic) that lives in thearea. This region consists of three regencies (beforeexpansion) which challenged from Mandar kingdoms,ethnic try again confirmed its glory by extending politicalrights to form an autonomous region through theestablishment of a new province in South Sulawesi.This paper focuses on problem, how is the struggleorder of forming new province in the former Mandarsection and why does formation movement appear inthe former Mandar section. By using descriptivequalitative approach which determines informantchosen focus on what is suggested by Patton (1994)where determining informant by using purposive way.The conceptual framework used from Fakih (2000);Nordliger (1994); Suzane Keller (1984); and RyassRasyid (2000).the finding of the research describes thatstruggle movement of forming new province in theformer Mandar section is a form of social movement tothe positive phenomenon as a constructive means tosocial struggle where this movement is coordinated byan institution as a historical flame product refers to anumber of activities to ease the movement pioneeredby intellectual and traditional elite.Key Words: Social Movement, Formation of Provincein the Former Section of Mandar; and ethnicity.